2007
DOI: 10.1177/1077801206297437
|View full text |Cite
|
Sign up to set email alerts
|

Differing Effects of Partner and Nonpartner Sexual Assault on Women's Mental Health

Abstract: This study contrasted the effects of intimate partner and nonpartner sexual assault on women's mental health among a sample (N=835) of low-income, ethnically diverse community women. Compared to sexual assault by a previous partner or by a non-intimate partner, sexual assault by a current partner was the strongest predictor of PTSD, stress, and dissociation. Non-intimate partner sexual assault was only a significant predictor of PTSD and only for African American women. These findings suggest that the victim-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 46 publications
3
105
1
Order By: Relevance
“…Thus it may be useful to educate college men and women on how to provide reactions to disclosure that allow the survivor to tell their story and communicate that they are believed and not to blame (Ullman, 1999). It is useful for college students to be aware that, contrary to the stereotype that rape is perpetrated by a stranger, the majority of assaults on college campuses are perpetrated by someone known to the victim (Koss, 1988) and are no less traumatic or serious than stranger rape (Temple, Weston, Rodriguez, & Marshall, 2007). Peers can also be educated on other common rape myths, including the myths that "women are never raped by their boyfriend" or "it isn't really rape if the woman doesn't physically resist" (Payne, Lonsway, & Fitzgerald, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Thus it may be useful to educate college men and women on how to provide reactions to disclosure that allow the survivor to tell their story and communicate that they are believed and not to blame (Ullman, 1999). It is useful for college students to be aware that, contrary to the stereotype that rape is perpetrated by a stranger, the majority of assaults on college campuses are perpetrated by someone known to the victim (Koss, 1988) and are no less traumatic or serious than stranger rape (Temple, Weston, Rodriguez, & Marshall, 2007). Peers can also be educated on other common rape myths, including the myths that "women are never raped by their boyfriend" or "it isn't really rape if the woman doesn't physically resist" (Payne, Lonsway, & Fitzgerald, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Sexual violence research findings on victim offender relationships and mental health are mixed [9][10][11] and no studies have Depressive symptoms after a sexual assault among women: understanding victim-perpetrator relationships and the role of social perceptions been reported from low and middle income settings.…”
Section: Introductionmentioning
confidence: 99%
“…Temple 11 reported that assault by a current partner was strongly predictive of PTSD, stress and disassociation while non-partner sexual assault was only associated with PTSD for African American women (and not for Euro-American and Mexican American Women). In a study of more than 1000 women Ullman 10 also found negative social reactions predictive of PTSD across all types of offenders.…”
Section: Introductionmentioning
confidence: 99%
“…After a trauma such as sexual assault, these CBAs are typically shattered (see Janoff-Bulman, 1992). As research has shown, the extent to which such world beliefs are shattered is associated with increased distress and psychopathology (Temple et al, 2007).…”
Section: Resourcefulness/problem Solutionmentioning
confidence: 99%
“…Although the experience of intimate partner sexual assault is no less common or serious than stranger rape (see Temple, Weston, Rodriguez, & Marshall, 2007), the experience may be so schema incongruent that the survivor may not conceptualize the experience as rape, instead internalizing a host of invalidating interpretations of the assault (Gidycz & Layman, 1996). Further, because intimate partner sexual assault is often underreported and stranger rape is conceptualized as ''real rape'' (Koss, 1985), survivors of acquaintance assault may face disbelief and stigma when seeking support from friends, family members, or health care providers (Filipas & Ullman, 2001).…”
mentioning
confidence: 98%